STUDI STATUS HARA N, P DAN K UNTUK TANAMAN PADI PADA LAHAN PASANG SURUT DI DESA SARANG BURUNG KOLAM KECAMATAN JAWAI KABUPATEN SAMBAS - Susi Sartika, Susi sartika (Jurnal Sains Pertanian Equator, 2016)
ABSTRACT This study aimed to determine the status of nutrients N, P and K at research site for the development of rice and fertilizer recommendation for tidal wetland in the study site. The research was conducted in Agustus - December 2015 in Sarang Burung Kolam village precisely in the hamlet Buluh Perindu Jawai Subdistrict Sambas Regency with a land area of 3,5 ha. The method used in this research was survey. Variables of observation in this research include pH, N-total, P-available, K-dd, DHL, pyrte test and calculation of fertilizer requirements. The result of analysis shows that pH is relatively netral "“ midly alkalis in 6,87 -7,90, nutrient status N is relatively high "“ very high that is 0,73 % - 1,25 %, P is relatively low, moderate, to vey high that is, 6,72 ppm, 8,17 ppm to 15,84 ppm, P total is relatively low to moderate that is, 18,66 ppm to 21,63 ppm, K-dd relatively moderate to high that is 0,52 "“ 0,85 cmol (+) kg-1, DHl is relatively low that is, 1,29 dS/m, contains harmless pyrte, ground water level is relatively shallow to withint that is, 18,20-21,00. Fertilizer recommendation in each site are T1 (229,82 kg urea/ha, 120,72 kg Sp-36/ha, 49,87 kg KCl/ha), T2 (254,86 kg urea/ha, 129,33 kg Sp-36/ha, 49,84 kg KCl/ha), T3 ( 255,39 kg urea/ha, 118,61 kg Sp-36/ha, 49,84 kg KCl/ha), T4 (254,86 kg urea/ha, 78,66 kg Sp-36/ha, 64,80 kg KCl/ha), T5( 228,36 kg urea/ha, 97,5 kg Sp-36/ha, 49,78 kg KCl/ha), T6 (253,82 kg urea/ha, 121,27 kg Sp-38/ha, 38,46 kg KCl/ha) dan T7 (254,34 kg urea/ha, 97,67 kg Sp-36/ha, 49,80 kg KCl/ha). Keywords : jawai, tidal, rice plant, nutrient status